Social Capital For Knowledge Management: The Case Of Small And Medium-Sized Enterprises In The Asia-Pacific Region - G. Roxas, Banjo (Asian Academy of Management (AAM), 2008)
This article proposes a conceptual framework that explains that the social capital of a community shapes the innovation performance of small and medium-sized enterprises (SMEs) through knowledge management within the firm. The study's significance stems from the unprecedented effort in explaining how community social capital matters in the innovation performance of SMEs, a departure from previous studies that have typically examined market-related or hierarchical social capital in the form of formal networks and directly linked them to a firm's innovation performance without due regard for knowledge management within the firm as an antecedent of organisational innovation performance. The aim is to stimulate further thinking and empirical research on the subject of social capital of a community in the SME and/or entrepreneurial context.